Circular agri-food approaches: will consumers buy novel products made from vegetable waste?. Issue 2 (4th May 2019) - McCarthy, Breda; Kapetanaki, Ariadne Beatrice; Wang, Pengji
ABSTRACT: This article discusses the challenges associated with managing waste in the horticultural sector by presenting the circular economy framework as a solution to the problem of food waste. The research focuses on consumers' role and value adding as one strategy that transforms food waste for reuse in accordance with a circular economy. A structured questionnaire was collected from a sample ( n  = 330) of Australian households to assess consumers' willingness buy food derived from underutilised biomass. The survey found half of the sample was willing to buy value-added food. Helping Australian farmers was the top-ranking factor driving demand. Awareness of the food waste problem is significant in distinguishing consumers who are willing to buy value-added food from those who are not. Marketing recommendations for communication design a circular economy are to stress empathy and care for farmers and highlight the consequences of food waste for both the natural environment and people.